Redesign UI/UX Website Menabung.id Menggunakan Metode User Centered Design dengan Evaluasi UX - Sirojul Munir; Syaffa Mufidah; Shelly Pramudiawardani; Muchamad Zainuri; Hanna Anggraini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The use of Menabung.id as a digital platform to record and monitor student savings in schools revealed limitations in both the user interface and user experience. Less intuitive navigation, inconsistent visual presentation, and suboptimal information display created obstacles for teachers and students in utilizing the system effectively. This situation highlighted the urgency of redesigning the UI/UX to make user interactions more comfortable, efficient, and effective, thereby achieving the goals of digitalizing administration and improving financial literacy. This study aimed to redesign the UI/UX of Menabung.id using the User-Centered Design (UCD) approach, placing users at the center of all design stages, including requirement analysis, prototype development, and evaluation. An interactive prototype was developed using Figma, and usability testing was conducted using the System Usability Scale (SUS) and Single Ease Question (SEQ) to measure system effectiveness and ease of use. The results indicated that the UCD-based redesign improved interface quality and user experience. SUS scores reached 81,3 for teachers and 82.5 for students, categorised as Excellent, while SEQ scores were 5.96 and 5.81, indicating a high level of task completion ease. These improvements included teacher and student dashboards, transaction history, savings schedules, real-time notifications, and an interactive chatbot. The findings demonstrated that user-centered design effectively enhanced usability and user satisfaction. Further research can complement the evaluation with eye-tracking or A/B testing methods and develop the system for mobile platforms to increase user accessibility.